Depeche Mode. Jacob Taubes between Politics, Philosophy, and Religion - Kopp-Oberstebrink, Herbert; Berlin, Zentrum für Literaturforschung; Sass, Hartmut von (Supplements to The Journal of Jewish Thought and Philosophy, 2022)
Jacob Taubes is one of the most significant intellectual figures in the more recent German intellectual scene-and beyond. However, Taubes was either dismissed as a highly controversial character, or as a mere commentator of ongoing debates, or the reception was restricted to his considerations on religion and the ambivalences of secularity. This volume challenges these reductions by putting Taubes' original, albeit marginalised, texts into new, sometimes surprising contexts. Furthermore, it relates familiar topics in his oeuvre to lesser-known themes that are still highly pertinent for contemporary discussions on faith, modernity, and the limits of politics.